Digital technology-driven rural common prosperity: a case study of China narrowing the income gap between urban and rural areas - Zhang, Zimo; Lu, Yimin (Frontiers in Sustainable Food Systems, 2025)
Enhancing rural digital connectivity constitutes a significant strategy employed by China to refine rural economic development and mitigate urban–rural income inequality. Utilizing provincial data on urban–rural income inequality and rural digital connectivity spanning from 2012 to 2021, this paper adopts a rigorous two-way fixed effect model to explore the intricate mechanism through which rural digital connectivity narrows urban–rural income inequality. The findings indicate that the impact of rural digital connectivity on urban–rural income inequality follows a U-shaped curve. Furthermore, a comprehensive mechanism analysis reveals that rural digital connectivity narrows urban–rural income inequality by refining industrial structures, stimulating digital commerce, and fostering industrial convergence in rural areas. It is noteworthy that rural digital connectivity exerts varying degrees of influence across different regions, with a more profound impact observed in highly urbanized provinces offering free shipping services. Ultimately, this paper presents pertinent policy implications aimed at bolstering rural digital connectivity and mitigating potential negative spillover effects through the implementation of rational resource distribution.